The Role of Academic Fraud as an Intervening Variable in Relationship of Determinant Factors Student Ethical Attitude - Budi Sulistiyo Nugroho; Made Ayu Anggreni; Mihrab Afnanda; Deddy Novie Citra Arta; Hendy Tannady (Departement of Mathematics Education, 2023)
The study aims to investigate how students' ethical behavior is influenced by their levels of intellectual, emotional, and spiritual intelligence, with educational fraud serving as a moderating factor. In order to gather the primary data for this study, 232 accounting students from 64 universities in Indonesia were given questionnaires. The information analysis method used in this study is partial least squares (PLS) with structural equation modeling (SEM) utilizing SmartPLS 3 software. The results of this study show that while religious and intellectual intelligence have a large and favorable influence on educational fraud, emotional intelligence has no discernible effect. Spiritual intelligence has the power to impact college students' moral behavior in a way that highbrow intelligence and emotional intelligence do not. Academic fraud has a big impact on how pupils act morally. According to this analysis, students' ethical behavior with instructional fraud as an intervening variable is partially and significantly influenced by highbrow intelligence and non-secular intelligence; in contrast, students' ethical behavior without educational fraud as an intervening variable is not influenced by emotional intelligence.